Financial Performance and Health Analysis of Islamic Banking Pre-Mega Merger (Equilibrium: Jurnal Ekonomi Syariah, 2022)
The Islamic banking industry has transformed into an industry with prospects that can surpass conventional banking. This study analyzes the effect of the financial performance and soundness of Bank Syariah Indonesia before the mega-merger on profitability. The research uses bank health indicators, including Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (OER), Net Operating Margin (NOM), and Return on Assets (ROA). The research method uses multiple linear regression. The results showed that CAR, NPF, and NOM did not affect ROA. However, FDR and OER affect ROA. Indonesian Islamic banks need to pay attention to the feasibility aspect of financing to avoid non-performing financing. Islamic banks use FDR and OER to increase their profitability because the conditions experienced by Bank Syariah Indonesia as the leading Islamic bank in Indonesia after the mega-merger, are considered capable of simultaneously representing.